IMGT/GeneInfo: enhancing V(D)J recombination database accessibility - Baum, Thierry-Pascal (Oxford University Press, 2004)
IMGT/GeneInfo is a user-friendly online information system that provides information on data resulting from the complex mechanisms of immunoglobulin (IG) and T cell receptor (TR) V(D)J recombinations. For the first time, it is possible to visualize all the rearrangement parameters on a single page. IMGT/GeneInfo is part of the international ImMunoGeneTics information system® (IMGT), a high-quality integrated knowledge resource specializing in IG, TR, major histocompatibility complex (MHC), and related proteins of the immune system of human and other vertebrate species. The IMGT/GeneInfo system was developed by the TIMC and ICH laboratories (with the collaboration of LIGM), and is the first example of an external system being incorporated into IMGT. In this paper, we report the first part of this work. IMGT/GeneInfo_TR deals with the human and mouse TRA/TRD and TRB loci of the TR. Data handling and visualization are complementary to the current data and tools in IMGT, and will subsequently allow the modelling of V(D)J gene use, and thus, to predict non-standard recombination profiles which may eventually be found in conditions such as leukaemias or lymphomas. Access to IMGT/GeneInfo is free and can be found at http://imgt.cines.fr/GeneInfo.